(untitled) (International journal of artificial intelligence, 2025)
This article explores the multifaceted nature of ethnographisms—lexical items that encode culturally specific practices, artifacts, institutions, or social norms—positioning them as critical markers at the intersection of language and culture. Moving beyond simple lexicography, this study argues that ethnographisms are invaluable data points for testing core hypotheses across the humanities and social sciences. Drawing on frameworks from linguistic anthropology, semantic typology, translation studies, and cognitive linguistics, the paper examines why these culture-bound terms merit focused interdisciplinary attention. We analyze how ethnographisms reveal fundamental questions regarding semantic universality versus cultural particularity, demonstrate the processes of cultural salience through lexicalization, and highlight the inherent challenges in achieving semantic equivalence during intercultural communication and translation. Ultimately, the study posits that analyzing ethnographisms—from kinship terms to ritual vocabulary—offers a powerful method for conducting 'thick description' of conceptual systems, thereby enriching our understanding of how language shapes and reflects human social reality.